Smart Cities: The Role of Artificial Intelligence in Urban Development - Wen, Zheyi (International Journal of Computer Science and Information Technology, 2025)
The rapid pace of urbanization has led to numerous challenges in managing cities efficiently and sustainably. Smart cities, which leverage advanced technologies such as artificial intelligence (AI), offer a promising solution to these challenges. This paper examines the role of AI in urban development, highlighting its applications, benefits, and potential limitations. By analyzing case studies and discussing policy implications, we aim to provide insights into how AI can contribute to the growth of smart cities.